Charitable Giving and NPOs Investment Decision in a Stochastic Dynamic Economy - Jiang, Han; Simons, Aggey (Université d'Ottawa | University of Ottawa, 2021)
This paper presents a dynamic model of charitable giving. At each period, donors contribute to a non-profit organization’s (NPO) endowment; the NPO provides a charitable good and invests in the financial market. Investments are made in a risky asset and a risk-free asset. To account for uncertainty, we introduce two types of shocks: donors’ income shock and financial market fluctuations. We show that the optimal share of disposable endowment, invested in risky asset, is constant. Donors’ strategy, whether to contribute or free-ride on the NPO’s investments, depends on donors’ shadow prices. Donors contribute when NPO’s endowment is relatively low. Large contribution levels encourage the NPO to participate in the capital market at the expense of providing charitable good. We show that the NPO prefers an environment with a lower rate of return on risk-free asset. NPO’s risk exposure to the financial market affects both NPO’s and donors’ decisions. However, risk exposures on donors’ side do not have any impact on parties’ decisions. Regulation analysis suggests that portfolio ceiling and provision floor are achievable.
Keywords: 2113E; Voluntary Contribution; Public Goods; Charitable Investment; Risk Preference; Stochastic Differential Game; Gauss-Markov Process; Hamilton-Jacobi-Bellman Equations